From theory to practice: Jewish and Arabs students in academia practice multicultural education. Issue 4 (18th May 2021) - Masry-Herzallah, Asmahan; Amzalag, Meital
Abstract : Purpose: The research examined factors of academic studies as perceived by Jewish and Arab students in Israel, and changes in their implementation of activities in a multicultural context in the field of education, comparing between undergraduates studying for a BA in education and graduate students for MA in education and attending a course titled "Multiculturalism in the Global Era". Design/methodology/approach: The findings are derived from a questionnaire distributed to Arab and Jewish students ( N  = 434), studying together in the Faculty of Education of one academic college in Israel. In total, 251 of them were graduate students, and 183 who were undergraduates. Findings: It was found that insofar as the students from either programme acquired knowledge and tools regarding multiculturalism, they reported (1) more positive attitudes regarding the "Other" group and regarding multiculturalism, (2) implementation of a larger number of activities relating to multiculturalism in the field of education, (3) Arab students performed more activities in multicultural contexts and (4) older students performed a larger number of activities in multicultural contexts. The research findings also indicated a direct relation between participation in the course and activities conducted in the field of education. In addition, students' acquiring of knowledge on multiculturalism mediated the relation between participation in the course and implementation of multicultural activities in the field of education. Originality/value: The research stresses the importance of higher education institutions in promoting knowledge and practice of multiculturalism in Israeli society.